The Norwood Stage 1 procedure - conduct of perfusion: 2017 Survey results from NPC-QIC member institutions. (November 2018) - Reagor, James A.; Clingan, Sean; Kulat, Bradley T.; Matte, Gregory S.; Voss, Jordan; Tweddell, James S.
Hypoplastic left heart syndrome (HLHS) is a rare and severe congenital cardiac defect. Approximately 1000 infants are born with HLHS in the United States every year. Healthcare collaboratives over the last decade have focused on sharing patient experiences and techniques in an effort to improve outcomes. In 2010, cardiologists and patient families joined together to improve the care of HLHS patients by forming the National Pediatric Cardiology Quality Improvement Collaborative (NPC-QIC). Sixty-six of the approximately 110 institutions caring for patients with HLHS in the United States and Canada are now members of NPC-QIC. In 2017, cardiovascular perfusionists joined the collaborative as another specialty involved in the care of HLHS patients. Perfusionists and cardiac surgeons developed the collaborative's first conduct of perfusion survey for the Norwood Stage 1 procedure, specifically targeting the provision of cardiopulmonary bypass for patients with HLHS. This manuscript discusses the results of this survey, unveiling a significant variance in the conduct of perfusion for this patient population.